On the Asymptotic Behavior of Solutions of a Singular Cauchy Problem - Zernov, A. E.; Meleshko, T. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We consider a singular Cauchy problem for a nonlinear differential equation unsolved with respect to the derivative of the unknown function. We prove the existence of continuously differentiable solutions, investigate their asymptotic behavior near the initial point, and determine their number.